2004
DOI: 10.3390/91000883
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Some Nitrososulfamide Compounds with Antitumor Activity

Abstract: Abstract:The lowest-energy conformations of four 2-chloroethylnitrososulfamides were determined using the MM+ molecular mechanics method as implemented in Hyperchem 6.0. Some of the calculated structural parameters, angles and bonds lengths were compared with the crystal structure data of N-nitroso-N-(2-chloroethyl)-N'-sulfamoylproline. Using MM+, AM1 and PM3 the anti conformation was predicted to be more stable than the syn conformation in each of these compounds. With these methods we found that the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…N-nitroso-N'-(2-chloroethyl)-N'-sulfamide piperidine (CENS) (Fig. 1) constitutes a new compound exhibiting an antitumoral activity and which is capable to replace chloroethylnitrosourea (CENU) [45][46][47][48][49][50][51][52]. Recently, it was shown that CENS have some instability and low solubility in water.…”
Section: Introductionmentioning
confidence: 99%
“…N-nitroso-N'-(2-chloroethyl)-N'-sulfamide piperidine (CENS) (Fig. 1) constitutes a new compound exhibiting an antitumoral activity and which is capable to replace chloroethylnitrosourea (CENU) [45][46][47][48][49][50][51][52]. Recently, it was shown that CENS have some instability and low solubility in water.…”
Section: Introductionmentioning
confidence: 99%